Biodegradable Hydrogel Bead of Casein and Modified Xanthan Gum for Controlled Delivery of Theophylline - K. Giri, Tapan; Thakur, Amrita; K. Tripathi, Dulal (Current Drug Therapy, 2016)
Objective: Interpenetrating polymer network (IPN) hydrogel beads have been prepared for the controlled release of theophylline. Method: Theophylline loaded IPN hydrogel beads of casein and sodium carboxymethyl xanthan (SCMX) were prepared by simple ionotropic gelation and covalent crosslinking method in an aqueous environment. Hydrogel beads were characterized by Differential scanning calorimetry (DSC), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and Scanning electron microscopy (SEM). Release of drug from beads has been investigated in pH 1.2 KCl/HCl buffer and pH 6.8 phosphate buffers. Results: Release of drug from beads has been investigated in pH 1.2 KCl/HCl buffer and pH 6.8 phosphate buffers. All the formulations exhibited slow drug release in pH 1.2 KCl/HCl buffer and the maximum drug release in 2 h was 20.45±0.31 %. The dissolution profiles of theophylline in phosphate buffer solutions (pH 6.8) from hydrogel beads also showed retarded release pattern. Retardation of drug release was observed with increasing casein concentration, glutaraldehyde (GA) concentration, and drug loading. However, increasing aluminium chloride (AlCl3) concentration showed a quicker drug release. Drug release from hydrogel beads followed Fickian and anomalous transport in both the dissolution medium. Conclusion: Sodium carboxymethyl xanthan and casein cross-linked with Al3+ and GA could be an appropriate matrix for the preparation of interpenetrating polymer network hydrogel beads for controlled release of theophylline.
Keywords: hydrogel beads